O papel das tecnologias digitais em disciplinas de álgebra linear a distância: possibilidades, limites e desafios - Chiari, Aparecida [UNESP] (2015)
The objective of this research is to understand the role of digital technologies (DT) in educational processes associated with Linear Algebra in four distance teacher education in mathematics courses linked to the Open University of Brazil (UAB), in the context of its Virtual Learning Environments (VLE). It is a qualitative study. The study and the analysis are guided by theoretical perspectives related to modes of description in Linear Algebra, the notion of humans-with-media, transactional distance and the role of interaction and collaboration in distance learning. Grounded Theory is used to analyze the data, which was produced from four sources: observation in virtual learning environments, interviews, educational projects and researcher's notes. Results show that two roles are evident (each treated as an analytic category): DT as promoting communication range and DT in building digital learning materials. Four properties of the first category were explored: content, agents, temporality and evaluation. For the second category, three properties were analyzed: content, nature and resources involved. The two categories were then integrated into one central category, which suggested that DT, the internet, and the use of VLE can turn the latter into Interactive Digital Didactic Material (IDDM) through the automatic registration of interactions. This transformation can take place via different languages, such as textual, audio-visual or multimodal. With respect to the linear algebra course, an imbalance in description mode approaches (formal, algebraic, and geometric) was noted, which stressed the need to encourage movement among them. This movement can be encouraged by the possibilities introduced by DT. The model constructed was used to identify patterns of use of technologies in the institutions as a way to validate the analysis and provoke reflections about the consistency between observed practices and institutional goals. In this...